2016
DOI: 10.1007/s00394-016-1285-y
|View full text |Cite
|
Sign up to set email alerts
|

Circulating ferritin concentrations are differentially associated with serum adipokine concentrations in Japanese men and premenopausal women

Abstract: Increased iron storage may be associated with higher circulating concentrations of leptin and visfatin in men and with lower concentrations of adiponectin in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
0
1
2
Order By: Relevance
“…Previously, we found a significant association of serum ferritin with insulin resistance, leptin and visfatin in men, but not in women . In the present study, however, there was no statistically significant sex difference in association between ferritin and type 2 diabetes.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Previously, we found a significant association of serum ferritin with insulin resistance, leptin and visfatin in men, but not in women . In the present study, however, there was no statistically significant sex difference in association between ferritin and type 2 diabetes.…”
Section: Discussioncontrasting
confidence: 91%
“…Previously, we found a significant association of serum ferritin with insulin resistance, leptin and visfatin in men, but not in women. 33,34 In the present study, however, there was no statistically significant sex difference in association between ferritin and type 2 diabetes. Two meta-analyses (one based on prospective studies in Western countries 35 , and another based on various types of studies in Western and Asian countries 17 ) reported no evidence of sex difference in association between ferritin and type 2 diabetes.…”
Section: Discussioncontrasting
confidence: 77%
“…In fact, sFT levels have been associated with the severity of COVID-19 disease progression, correlating higher FT levels with fatal outcomes over time [49]. Other studies have pointed out that circulating FT levels are associated with dysfunctions of the adipose tissue [50,51] and linked with increased risk of cardiovascular disturbances [52]. Moreover, because FT secretion is stimulated by pro-inflammatory cytokines and FTH has pro-inflammatory effects, it has been hypothesized that elevated FT levels in the serum may not only be a consequence of inflammation but also a part of the pathogenic mechanism of the disease, thus contributing to the observed inflammatory burden [53,54].…”
Section: Ferritinmentioning
confidence: 99%